2019
DOI: 10.1021/acs.jmedchem.8b01294
|View full text |Cite|
|
Sign up to set email alerts
|

Conversion of Quinazoline Modulators from Inhibitors to Activators of β-Glucocerebrosidase

Abstract: Gaucher's disease is a lysosomal disease caused by mutations in the β-glucocerebrosidase gene (GBA1, GCase) that have been also linked to increased risk of Parkinson's disease and Diffuse Lewy Body Dementia. Prior studies have suggested that mutant GCase protein undergoes misfolding and degradation and therefore stabilization of the mutant protein represents an important therapeutic strategy in synucleinopathies. In this work, we present a structure activity relationship (SAR) study of quinazoline compounds th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…In these models, S-181 partially restored lysosomal function and lowered the accumulation of oxidized dopamine, GluCer, and α-synuclein. Similar findings were also obtained treating mice carrying GBA heterozygous mutations [36].…”
Section: Gcase Activitysupporting
confidence: 81%
“…In these models, S-181 partially restored lysosomal function and lowered the accumulation of oxidized dopamine, GluCer, and α-synuclein. Similar findings were also obtained treating mice carrying GBA heterozygous mutations [36].…”
Section: Gcase Activitysupporting
confidence: 81%
“…Coupling with aliphatic aldehydes was also feasible, yielding 2,4-dialkylsubstituted quinazolines 3ae, 3ag, 3ah in good yields (entries 5-7). Next, 1-(6-aminobenzo[d] [1,3]dioxol-5-yl)ethan-1one was employed for the reaction with different aldehydes, producing 3ba, 3bb, 3bc, and 3bd in 74%, 78%, 75%, and 72% yields, respectively (entries 8-11). Moving to the transformation of 1-(2-amino-4,5-dimethoxyphenyl)ethan-1-one with several aldehydes, 3ca, 3cb, 3cc, and 3cd were generated in 72%, 70%, 75%, and 69% yields, respectively (entries 12-15).…”
Section: Resultsmentioning
confidence: 99%
“…Quinazolines and their derivatives are a privileged class of nitrogen-containing heterocyclic compounds, normally occurring in a variety of natural products and synthetic chemicals with a wide spectrum of biological and medicinal activities. [1][2][3][4] Due to their pharmaceutical applications and signicant biological value, a variety of methodologies have been explored for the synthesis of these structures. Typical approaches started from ortho-functionalized anilines and derivatives, such as 2-carbonyl anilines, 5 2-aminobenzylamines, 6 and 2-aminobenzonitriles.…”
Section: Introductionmentioning
confidence: 99%
“…The recent co-crystallization of the Gcase with a quinazoline derivative not only helped to understand the mechanism of non-iminosugar inhibitory PC but also allowed the discovery of an allosteric binding site which could be responsive to activators (PDB code 5LVX) [ 63 ]. Thanks to a broad structure-activity relationship study in this compound series [ 62 , 64 ], Silvermann et al, recently found that N -methylation of some of the quinazoline inhibitors derivatives turned them into activators. Compound S-181 (( S )- N -((2,3-dihydrobenzo[b][1,4]dioxin-2-yl)methyl)- N -methyl-2-(pyridin-3-yl)quinazolin-4-amine, Table 1 ) was highlighted as the most potent non-inhibitory Gcase PC with specificity towards the Gcase and not α-glucosidases or galactosidases [ 64 ].…”
Section: Second-generation Pharmacological Chaperones Against Lsdsmentioning
confidence: 99%